The Mexican transpacific : Nikkei writing, visual arts, and performance - López-Calvo, Ignacio (Critical Mexican studies., 2022)
"An analysis of writing, as well as visual and performance arts, by Mexicans of Japanese ancestry, which explores Chinese Mexican self-definition and its implications for Mexican national identity"--